The spy who knew too much : an ex-CIA officer's quest through a legacy of betrayal - Blum, Howard (Harper, an imprint of HarperCollinsPublishers, 2022)
A true-life tale of vindication and redemption relates how retired spy Tennant Bagley got back into the game to solve a strange death, and reconciled with his daughter, a CIA officer, who married into the very family that derailed his own CIA career.